2013
DOI: 10.1007/s00011-013-0687-z
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1 (fractalkine) and TNFα production by perfused human placental lobules under normoxic and hypoxic conditions in vitro: the importance of CX3CR1 signaling

Abstract: Objective Inflammation and hypoxia activate the fractalkine (CX3CL1) receptor (CX3CR1)-related signaling pathway. Tumor necrosis factor alpha (TNFα) induces CX3CL1, influencing a mechanism of CX3CL1 autoregulation by CX3CR1 expression. We compared spontaneous and lipopolysaccharide (LPS)-induced CX3CL1 and TNFα production by human placenta under normoxic vs. hypoxic conditions, with respect to CX3CR1 expression and its functional status.MethodsPlacental lobules of term placentae (N = 24) were perfused extracor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
0
16
1
Order By: Relevance
“…CX3CL1 is important in the recruitment of inflammatory cells into the vascular wall in endothelial cell injury (12,13). Previous studies have reported that TNF-α stimulates the CX3CL1/CX3CR1 inflammatory signaling pathway, whereas our previous studies revealed that the expression levels of TNF-α, CX3CL1 and CX3CR1 were significantly increased in rats with pulmonary embolism (3,14). Certain studies have reported that the presence and the stimulation of the CX3CL1 receptor, CX3CR1, is correlated with the reduced release of IL-1β and TNF-α (15,16).…”
Section: Discussioncontrasting
confidence: 62%
“…CX3CL1 is important in the recruitment of inflammatory cells into the vascular wall in endothelial cell injury (12,13). Previous studies have reported that TNF-α stimulates the CX3CL1/CX3CR1 inflammatory signaling pathway, whereas our previous studies revealed that the expression levels of TNF-α, CX3CL1 and CX3CR1 were significantly increased in rats with pulmonary embolism (3,14). Certain studies have reported that the presence and the stimulation of the CX3CL1 receptor, CX3CR1, is correlated with the reduced release of IL-1β and TNF-α (15,16).…”
Section: Discussioncontrasting
confidence: 62%
“…The activation of signaling pathways involved in CX3CL1/CX3CR1 regulation in response to oxygen deprivation (e.g., pro-angiogenic) or related to cancerous mutations have been studied by many researchers. Changes in the cytokine network including TNF-α and CX3CL1 production and their respective receptor expression were striking [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As we known, CX3CL1 is one of the pivotal chemokines involved in T cell migration17. In the serum and synovial homogenate of CIA rats, we detected much higher concentrations of CX3CL1 than that in normal rats (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…5C). The level of CX3CL1 is reported to be induced by TNF-α and other pro-inflammatory cytokines17. Both paroxetine and MTX could reduce the level of CX3CL1 in serum and synovial tissues but with different extent.…”
Section: Resultsmentioning
confidence: 99%